2009
DOI: 10.1111/j.1365-2958.2009.06799.x
|View full text |Cite
|
Sign up to set email alerts
|

NsrR targets in the Escherichia coli genome: new insights into DNA sequence requirements for binding and a role for NsrR in the regulation of motility

Abstract: SummaryThe Escherichia coli NsrR protein is a nitric oxidesensitive repressor of transcription. The NsrRbinding site is predicted to comprise two copies of an 11 bp motif arranged as an inverted repeat with 1 bp spacing. By mutagenesis we confirmed that both 11 bp motifs are required for maximal NsrR repression of the ytfE promoter. We used chromatin immunoprecipitation and microarray analysis (ChIPchip) to show that NsrR binds to 62 sites close to the 5Ј ends of genes. Analysis of the ChIP-chip data suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
136
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 126 publications
(138 citation statements)
references
References 63 publications
(143 reference statements)
2
136
0
Order By: Relevance
“…1). The tynA, feaB and fliA promoters are weakly regulated by NsrR, meaning that these are only modestly derepressed in an nsrR mutant (Rankin et al, 2008;Partridge et al, 2009). These promoters are more strongly repressed when the nsrR start codon is AUG than when it is GUG (Fig.…”
Section: Nsrr Expression Is Limited At the Level Of Translation Initimentioning
confidence: 99%
See 4 more Smart Citations
“…1). The tynA, feaB and fliA promoters are weakly regulated by NsrR, meaning that these are only modestly derepressed in an nsrR mutant (Rankin et al, 2008;Partridge et al, 2009). These promoters are more strongly repressed when the nsrR start codon is AUG than when it is GUG (Fig.…”
Section: Nsrr Expression Is Limited At the Level Of Translation Initimentioning
confidence: 99%
“…Thus, we speculate that inefficient translation maintains a low abundance of NsrR, while still allowing high-level expression of downstream genes. Furthermore, we have shown that the overexpression of nsrR severely represses some genes that are only modestly derepressed by deletion of nsrR (Rankin et al, 2008;Partridge et al, 2009). Thus, the abundance of NsrR seems to be poised in such a way that an increase in NsrR levels has measurable consequences for the expression of some NsrR targets.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations